Disease burden of anxiety disorders in China in 1990 and 2019: a comparative analysis among global regions with different sociodemographic index - Xiao-qing XIA; Yan ZHAO; Meng-xuan HAO (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo compare the trend in disease burden of anxiety disorders between China and global regions with different socio-demographic index (SDI) in 1990 and 2019 for providing evidence to rational allocation of health resources and formulation of anxiety prevention and control strategies. MethodsThe study data were from the Global Burden of Disease Study (GBD 2019). Incidence, years lived with disability (YLDs), age-standardized incidence, age-standardized prevalence, and age-standardized YLDs rate were applied to compare the disease burden of anxiety disorders and its changing trend among residents in China to those of residents in global regions with different SDI in 1990 and 2019. ResultsAmong Chinese residents, the incidence number and YLDs of anxiety disorders increased from 6 667 495 and 4 045 138 person-years in 1990 to 7 285 634 and 4 574 328 person-years in 2019, with the increase rates of 9.37% and 13.08%, respectively. Compared with those in the residents of global regions with different SDI, the age-standardized incidence rate, age-standardized prevalence rate, and age-standardized YLDs rate of anxiety disorders in China in 1990 and 2019 were all at low levels and showed decreasing trend; the age-standardized incidence rate decreased from 556.56/100 000 to 522.97/100000, with a change rate of − 6.03%; the age-standardized prevalence rate decreased from 3507.31/100 000 to 3 164.18/ 100 000, with a change rate of − 9.78%; the age-standardized YLDs rate decreased from 337.47/100000 to 306.02 /100000, with a change rate of − 9.32%. In contrast, the age-standardized incidence rate, age-standardized prevalence rate, and age-standardized YLDs rate of anxiety disorders among populations in the global regions with high SDI were all at high levels and increased from 679.46/100 000, 4637.21/100 000, and 441.19/100 000 in 1990 to 710.54/100 000, 4 806.55/100 000 and 456.89/100 000 in 2019, with the changing rates of 4.57%, 3.65%, and 3.56%. In 1990 and 2019, the burden of anxiety disorders in female residents in China and in global regions with different SDI were much higher than that in male residents. In comparison with those in the males, higher age-standardized rates (for 100 000 population) were observed in the females in China and in global regions with high SDI when examining anxiety disorders' incidence (630.04 vs. 425.33 and 837.43 vs. 591.16), prevalence (3 912.33 vs. 2 453.91 and 6 168.67 vs. 3 482.78), and YLDs (377.20 vs. 238.88 and 582.82 vs. 334.80). ConclusionCompared with the residents in global regions with different SDI, the disease burden of anxiety disorders among Chinese residents decreased greatly from 1990 to 2019 and the disease burden was heavier in the female populations than in the male populations both in China and in global regions with different SDI.